Gut microbiota dependant trimethylamine N-oxide and hypertension - Mutengo, Katongo H.; Masenga, Sepiso K.; Mweemba, Aggrey; Mutale, Wilbroad; Kirabo, Annet (Frontiers in Physiology, 2023)
The human gut microbiota environment is constantly changing and some specific changes influence the host’s metabolic, immune, and neuroendocrine functions. Emerging evidence of the gut microbiota’s role in the development of cardiovascular disease (CVD) including hypertension is remarkable. There is evidence showing that alterations in the gut microbiota and especially the gut-dependent metabolite trimethylamine N-oxide is associated with hypertension. However, there is a scarcity of literature addressing the role of trimethylamine N-oxide in hypertension pathogenesis. In this review, we discuss the impact of the gut microbiota and gut microbiota dependent trimethylamine N-oxide in the pathogenesis of hypertension. We present evidence from both human and animal studies and further discuss new insights relating to potential therapies for managing hypertension by altering the gut microbiota.